PENGGUNAAN MODUL PEMBELAJARAN BAHASA INDONESIA PADA SISWA KELAS VIII UPT SMP NEGERI 3 PONGGOK - Nur Istiamin (Dharmas Education Journal (DE_Journal), 2020)
The covid-19 pandemic changed the learning system in Indonesia from face-to-face to online-based. Many strategies are used by teachers to keep learning conducive, one of which is the use of learning modules. This research purpose to describe the use of Indonesian learning modules in VIII class at UPT SMP Negeri 3 Ponggok. This research has a type of qualitative research, because it has data in the form of words. The research approach used is descriptive research. The research subject to be analyzed is the Indonesian learning module, with the object of class VIII-C and class VIII-D. The data collection techniques used were documentation and quistionnare. After the data is collected, it will then be processed using the Miles and Huberman technique, which includes several stages; data reduction, data presentation, and drawing conclusions. The results obtained are expected to be a reference for teachers in conditioning Indonesian language learning activities in the midst of the covid-19 pandemic. Keywords: covid-19, learning module, online, VIII class students.